Cardiac events in football and strategies for first-responder treatment on the field - Schmied, C.; Drezner, J.; Kramer, E.; Dvorak, J. (British Journal of Sports Medicine, 2013)
Background: The incidence and outcomes of sudden cardiac arrest (SCA) and global strategies for prevention of sudden cardiac death (SCD) in football are not known. The aim of this study was to estimate the occurrence of cardiac events in football and to investigate the preventive measures taken among the Fédération International de Football Association (FIFA) member associations internationally.